1980
DOI: 10.1254/jjp.30.587
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polyamines on Ethylmorphine N-Demethylation in Rat Liver Microsomes

Abstract: Abstract-Effects of calcium antagonists and lidocaine on the conduction delay observed in the ischemic myocardium were studied in 24 open-chest anesthetized dogs. Acute myocardial ischemia was produced by complete occlusion of the left anterior descending coronary artery (LAD) for 5 or 10 minutes. The conduction time was measured from the initial deflection of V waves on the His bundle electrograms to the major deflection of the bipolar electrograms recorded from the ischemic and non-ischemic subepicardium und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…The slowing of the ROC of myocardial action potentials during ischaemia in vivo and during SI in vitro has been attributed, by many previous workers, to alterations in cellular calcium metabolism (Wojtczak, 1979;Nakaya et al, 1980;Kimura et al, 1982;Gettes et al, 1985). It is well established that conduction of action potentials through the myocardium depends upon a selective flow of ionic current through specialised regions of low electrical resistance between adjacent cells (DeMello, 1982).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The slowing of the ROC of myocardial action potentials during ischaemia in vivo and during SI in vitro has been attributed, by many previous workers, to alterations in cellular calcium metabolism (Wojtczak, 1979;Nakaya et al, 1980;Kimura et al, 1982;Gettes et al, 1985). It is well established that conduction of action potentials through the myocardium depends upon a selective flow of ionic current through specialised regions of low electrical resistance between adjacent cells (DeMello, 1982).…”
Section: Discussionmentioning
confidence: 93%
“…These specialized regions of low electrical resistance are disrupted, lost or occluded when the cytoplasmic calcium concentration rises (DeMello, 1975), as it does during ischaemia, thus slowing the ROC of the action potential. Several groups of workers have demonstrated that slow channel calcium entry blockers of various chemical types (Nakaya et al, 1980;Kimura et al, 1982;Gettes et al, 1985), as well as certain intracellular calcium antagonists (Anno et al, 1986), inhibit the slowing of the ROC of action potentials during exposure of the myocardium to ischaemia or SI. The ability ofverapamil in the present experiments, therefore, to inhibit SI-induced slowing of the ROC extends to the rat the findings in other species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diltiazem and verapamil were shown to protect against all aspects of the response to SI. Previous workers have shown that these agents protect ventricular muscle against ischaemia-induced and hypoxia-induced shortening of refractory periods and slowing of CV (Elharrar et al, 1977;Nakaya et al, 1980;Fujimoto et al, 1981;Kimura et al, 1982;1983;Peter et al, 1982;1983;Gettes et al, 1985;Fleet et al, 1986), against the associated contracture (Henry et al, 1977;Poole-Wilson et al, 1982;1984;Cavero et al, 1983;Fitzpatrick & Karmazyn, 1984;Henry, 1984;Ferrari et al, 1986;Piacenza et al, 1986), and against the mitochondrial structural alterations (Rahamathulla et al, 1983). In the present experiments, verapamil and diltiazem protected the atria only at concentrations which exerted a negative inotropic effect in NS.…”
Section: Dijscus;onmentioning
confidence: 98%
“…The precise mechanism of this protective action is unclear but there appear to be two main and related possibilities: (i) Nifedipine abolishes abnormal automaticity in Purkinje fibres obtained from canine subendocardium 24 h after acute coronary artery ligation, as well as that induced in normal Purkinje fibres following exposure to barium chloride (Dangman & Hoffman, 1980). (ii) Nifedipine reduces the conduction delay which occurs within 5-10 min of the onset of acute myocardial ischaemia in dogs (Nakaya, Hattori & Kanno, 1980). This could result from a diminished degree of ischaemic injury as a result of increased blood flow, a 'sparing' effect on endogenous energy resources and/or a reduced intracellular sequestration of the metabolic byproducts of ischaemia.…”
Section: Introductionmentioning
confidence: 99%